(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
Occurrences of natural disasters are highly unpredictable. Anyone could be considered at risk. This study assessed the knowledge and practices of Ilocanos Elementary School teachers, pupils, and household heads of Barangay Ilocanos Sur and Ilocanos Norte as a basis in the formulation of a Strategic Disaster Risk Reduction Management Plan. A descriptive research design was used in this study. A survey questionnaire was used to determine the level of knowledge and practices of the respondents. Respondents are pupils and teachers of Ilocanos Elementary School and household heads from Ilocanos Norte and Ilocanos Sur, City of San Fernando La Union. The findings of this research showed that the level of knowledge of the respondents on disaster management and resiliency was very high. Moreover, results revealed that there is a high level of implementation as rated by three groups of respondents. It is concluded that the Ilocanos Community manifested a commendable performance along with knowledge, practice, and implementation. The Strategic DRRM Plan is recommended for adoption to sustain and further advance the status of the community in DRRM management. Further research is recommended to be conducted within a larger scope of the population as a follow-up study.